Erosion-corrosion characteristics of spark plasma sintered pure nickel in simulated mine water. (May 2017) - Ige, O.O.; Aribo, S.; Obadele, B.A.; Langa, T.; Olubambi, P.A.
Abstract: This study estimates the impact of shear stress and solid particles on the erosion-corrosion behaviour of spark plasma sintered pure nickel in simulated mine water. Rotating cylinder electrode system was employed to carry out the erosion-corrosion tests by weight-loss and electrochemical measurements. Corroded coupons were examined with the aid of microscope to assess the surface morphology. The gravimetry data was inconsistent with both weight gain and weight loss recorded. The impact of the hydrodynamic parameters was correlated with the pitting resistance and re-passivation behaviour of the sintered nickel, while the morphology results showed minimal general attack and severe localised corrosion. Graphical abstract: fx1 Highlights: Sintered Ni were assessed by gravimetric, potentiodynamic polarization, and cyclic potentiodynamic polarization techniques. Erosion-corrosion behaviour of SPS nickel is related with repassivation, pitting, and passive potentials. Total weight loss data were inconsistent. Estimating the synergistic/additive effect will be difficult. Impact of shear stress on localised corrosion data is examined.